Existential vulnerability: toward a psychopathology of limit situations - Fuchs, Thomas (Psychopathology, 2013)
Jaspers' concept of limit situations seems particularly appropriate not only to elucidate outstanding existential situations in general, but also basic preconditions for the occurrence of mental disorders. For this purpose, the concept is first explained in Jaspers' sense and then related to an ‘existential vulnerability' of mentally ill persons that makes them experience even inconspicuous events as distressing limit situations. In such situations, an otherwise hidden fundamental condition of existence becomes manifest for them, e.g. the fragility of one's own body, the inevitability of freedom, or the finiteness of life. This fundamental condition is found unbearable and, as a reaction, gives rise to mental illness. This concept of existential vulnerability is illustrated by some psychopathological examples.
Gesehen am 23.10.2020